PEMBERIAN PUPUK ABG (Amazing Bio Growth) DAN PUPUK KOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI HIJAU (Brassica juncea L. Coss) - Asmara Sari Nasution; Awalluddin -; M. Said Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The research on the application of fertilizer ABG (Bio Amazing Growth) and compost on the growth and yield of mustard greens (Brassica juncea L. Coss) has been carried out by using a randomized block design (RBD) consists of a two-factor factorial researched and 3 replications. ABG fertilizer treatments showed significant effect on the observed parameters such as plant height, leaf number and leaf area. But showed no real effect on the other parameters. Compost fertilizer treatments showed significant effect on all parameters except the parameter observations shoot root ratio shows no real effect. The interaction of fertilizer treatment and fertilizer Compost ABG showed significant effect on leaf area observed parameters, but the effect is not significant on the observation parameters plant height, number of leaves, root shoot ratio.Keywords: fertilizer ABG, compost, growth, production of green cabbage